Five Year Plan 1978-83 Draft Proposals Volume II Sectoral Programmes - Government of Meghalaya - Planning Commission (Planning Commission, 1978)
Achievements during 1974-78-The primary objectives of the Plan were to increase the production of food grains, commercial crops and horticultural crops in the State. Emphasis, had, therefore been laid on the use of improved methods of cultivation, the use of organic manures and chemical fertilizers, the use of high yielding varieties of seeds/ improved seeds. the schemes for protection of plants from pests and diseases and also for expansion of the area under rabi cultivation were intensified. Food grains Production. At the beginning of the fourth plan food grains production in the State was estimated at 1.17 lakhs tonnes. By the end of the fourth Plan, i.e., by the end of 1973-74, food grain Production stood at 1.25 lakh tonnes, showing an annual growth rate of approximately 1 1.4 per cent.
Government of Meghalaya Planning Department